Trajetórias de cineastas negras brasileiras - Letícia Souza Ribeiro da Costa (2020)
The objective of this research was to understand black Brazilian women filmmakers trajectories, that was part of Coletiva Malva Movie Show in Belo Horizonte - Minas Gerais. We investigated how black Brazilian filmmakers perceive themselves as black women, how they inserted themselves in the cinematographic field and whether the films produced by them dialogue with their life trajectories. We investigate five black women filmmakers trajectories: Labibe Araújo (MG), Viviane Ferreira (BA), Rejane Neves (RJ), Sabrina Fidalgo (RJ), and Mariana Luiza (MG). Documentary analysis and narrative interview were adopted as methodological resources in which were carried out in two stages. In the first, the registration forms for the Coletiva Malva Shows were analyzed which helped in choosing the filmmakers. In the second, narrative interviews were conducted with the selected women filmmakers. In theoretical terms, the work was based on a dialogue between Black Cinema, Black Movements and Black Women Movements theorists. As well as theorists who discuss black identities and blackness in order to understand the processes. Thus, that enable and interfere in the trajectories of black Brazilian women as filmmakers. The result of the research reveals that, for the interviewees, being a filmmaker does not separate them from the fact of being black women. In addition, the Black Cinema ends up constituting itself in its trajectories as a place of affirming its presence, going beyond a field of professional performance.